Measurement Across the Sciences Developing a Shared Concept System for Measurement - Mari, Luca; Wilson, Mark; Maul, Andrew (Springer Series in Measurement Science and Technology,, 2023)
This open access book proposes a conceptual framework for understanding measurement across a broad range of scientific fields and areas of application, such as physics, engineering, education, and psychology. It addresses contemporary issues and controversies within measurement in light of the framework, including operationalism, definitional uncertainty, and the relations between measurement and computation, and describes how the framework, operating as a shared concept system, supports understanding measurement's work in different domains, using examples in the physical and human sciences. This revised and expanded second edition features a new analysis of the analogies and the differences between the error/uncertainty-related approach adopted in physical measurement and the validity-related approach adopted in psychosocial measurement. In addition, it provides a better analysis and presentation of measurement scales, in particular about their relations with quantity units, and introduces the measurand identification/definition as a part of the "Hexagon Framework" along with new examples from the physical and psychosocial sciences. Researchers and academics across a wide range of disciplines including biological, physical, social, and behavioral scientists, as well as specialists in measurement and philosophy appreciate the work's fresh and provocative approach to the field at a time when sound measurements of complex scientific systems are increasingly essential to solving critical global problems.